Detailed characterization of SARS-CoV-2-specific T and B cells after infection or heterologous vaccination - Lo Tartaro, Domenico; Paolini, Annamaria; Mattioli, Marco; Swatler, Julian; Neroni, Anita; Borella, Rebecca; Santacroce, Elena; Di Nella, Alessia; Gozzi, Licia; Busani, Stefano; Cuccorese, Michela; Trenti, Tommaso; et al. (Frontiers in Immunology, 2023)
The formation of a robust long-term antigen-specific memory both humoral and cell-mediated is created after SARS-CoV-2 infection or vaccination. Here, by using polychromatic flow cytometry and sophisticated data analyses, we deeply investigated the magnitude, phenotype and functionality of SARS-CoV-2-specific immune memory in two groups of healthy subjects after heterologous vaccination, compared to a group of subjects who recovered from SARS-CoV-2 infection. We find that COVID-19 recovered patients show different long-term immunological profile compared to donors that had been vaccinated with three doses. Vaccinated individuals display a skewed Th1 Ag-specific T cells polarization and higher percentage of Ag-specific and activated memory B cells expressing IgG compared to patients who recovered from severe COVID-19. Different polyfunctional properties characterize the two groups: recovered individuals show higher percentages of CD4+ T cells producing one or two cytokines simultaneously, while vaccinated are distinguished by highly polyfunctional populations able to release four molecules such as CD107a, IFN-g, TNF and IL-2. These data suggest that functional and phenotypic properties of SARS-CoV-2 adaptive immunity differ in recovered COVID-19 individuals and vaccinated ones.